A cellular census of human peripheral immune cells identifies novel cell states in lung diseases - Dongli Song (Wiley, 2021)
Abstract Increasing evidence supports a central role of the immune system in lung diseases. Understanding how immunological alterations between lung diseases provide opportunities for immunotherapy. Exhausted T cells play a key role of immune suppression in lung cancer and chronic obstructive pulmonary disease was proved in our previous study. The present study aims to furthermore define molecular landscapes and heterogeneity of systemic immune cell target proteomic and transcriptomic profiles and interactions between circulating immune cells and lung residential cells in various lung diseases. We firstly measured target proteomic profiles of circulating immune cells from healthy volunteers and patients with stable pneumonia, stable asthma, acute asthma, acute exacerbation of chronic obstructive pulmonary disease, chronic obstructive pulmonary disease and lung cancer, using single‐cell analysis by cytometry by time‐of‐flight with 42 antibodies. The nine immune cells landscape was mapped among those respiratory system diseases, including CD4+ T cells, CD8+ T cells, dendritic cells, B cells, eosinophil, γδT cells, monocytes, neutrophil and natural killer cells. The double‐negative T cells and exhausted CD4+ central memory T cells subset were identified in patients with acute pneumonia. This T subset expressed higher levels of T‐cell immunoglobulin and mucin domain‐containing protein 3 (Tim3) and T‐cell immunoreceptor with Ig and ITIM domains (TIGIT) in patients with acute pneumonia and stable pneumonia. Biological processes and pathways of immune cells including immune response activation, regulation of cell cycle and pathways in cancer in peripheral blood immune cells were defined by bulk RNA sequencing (RNA‐seq). The heterogeneity among immune cells including CD4+, CD8+ T cells and NK T cells by single immune cell RNA‐seq with significant difference was found by single‐cell sequencing. The effect of interstitial telocytes on the immune cell types and immune function was finally studied and the expressions of CD8a and chemokine C–C motif receptor 7 (CCR7) were increased significantly in co‐cultured groups. Our data indicate that proteomic and transcriptomic profiles and heterogeneity of circulating immune cells provides new insights for understanding new molecular mechanisms of immune cell function, interaction and modulation as a source to identify and develop biomarkers and targets for lung diseases.